Comportamentos mecânico e metalúrgico de junta soldada em aço ASTM A182 F22 aplicado na indústria offshore - Garcia, Douglas Neves (2018)
The present work evaluated the mechanical and metallurgical behavior of the ASTM A182 F22 and X80 steel weld joints with different filler metals (AWS ERNiCrMo-3, ER 309L-Si, AWS ER 80S-G) applied in the offshore industry. The application of the Higuchi method on ASTM A182 F22 steel deposition in a buttery layer was analyzed in order to eliminate the need to use a heat stress relief treatment (HSRT). Hardness, microhardness, tensile and fracture tests were implemented to evaluate the mechanical properties of the buttery. The hydrogen effect on the mechanical properties in welded joints was also evaluated through the tensile test. The microstructural characterization of buttery interfaces was made by optical microscopy, scanning electron microscopy and EDS analysis. The Higuchi method led to reduction of the hardness values in ZAC close to 280 HV, however these values were over the maximum value required by the NACE standard (<250 HV). In the dissimilar interface of buttery there was a formation of partially mixed zone (PMZ). The PMZs showed high hardness points, even with a HSRT, and was not possible to temper these areas. The interface formed with the 80S-G weld metal did not present the PMZs. The hydrogenated tensile test samples demonstrated a reduction on F22 mechanical properties. The hydrogenated samples taken from the welded joints failed in the base metal indicating that the presence of the hydrogen in the F22 structure change the fracture mode from ductile to brittle. The fracture tests did not show differences of tenacity between dissimilar (ERNiCrMo-3) and similar (80SG) interfaces and the results indicated that the beneficial effect of HSRT and ZAC tempering overlapped the detrimental effect of decarburizing in dissimilar interface.